2008
DOI: 10.1139/g08-041
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in situ hybridization and characterization of the SalI family of satellite repeats in the Haliotis L. species (abalone) of the Northeast Pacific

Abstract: The SalI satellite repeat previously identified in Haliotis L. (abalone) was thought to be present in H. rufescens and absent in H. fulgens. However, we show here that SalI is also found in H. fulgens and is not useful for screening hybrid individuals bred in aquaculture or occurring naturally in the wild. SalI is a family of predominantly subtelomeric tandemly repeated sequences, and sequenced clones revealed clustering to species and little intraspecific variation. Analysis of SalI sequence divergence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…"Masyarakat dengan biaya marjinal nol" ini telah lama digembargemborkan sebagai model bisnis baru (Rifkin, 2014), tetapi semakin menunjukkan keterbatasannya baik dalam hal masalah privasi orang maupun dalam hal dampak ekonomi dan sosialnya, seperti yang telah dibahas sebelumnya. Salah satu solusi untuk mengatasi masalah ini adalah konsumen terus membagikan data mereka secara bebas tetapi membatasi penggunaannya untuk tujuan tertentu yang hanya memberikan peluang keuntungan yang terbatas (Arrieta- Ibarra. et al;.…”
Section: Kelemahan Artificial Intelligenceunclassified
“…"Masyarakat dengan biaya marjinal nol" ini telah lama digembargemborkan sebagai model bisnis baru (Rifkin, 2014), tetapi semakin menunjukkan keterbatasannya baik dalam hal masalah privasi orang maupun dalam hal dampak ekonomi dan sosialnya, seperti yang telah dibahas sebelumnya. Salah satu solusi untuk mengatasi masalah ini adalah konsumen terus membagikan data mereka secara bebas tetapi membatasi penggunaannya untuk tujuan tertentu yang hanya memberikan peluang keuntungan yang terbatas (Arrieta- Ibarra. et al;.…”
Section: Kelemahan Artificial Intelligenceunclassified
“…The occurrence of variable repeat sequence families is a generalized property of sub-telomeric regions across a broad range of species [94][95][96][97][98]. It appears that these regions of the genome have a propensity to accumulate repetitive DNA, with ectopic recombination being invoked as the key driver of this variation.…”
Section: Sub-telomeric Sequences-rapid Evolutionmentioning
confidence: 99%
“…However, it was absent from the black and green species and it was suggested that this DNA satellite sequence could be used to identify hybrids. However, Hernández- Ibarra et al (2008) discovered that SalI is also found in green abalone (H. fulgens) and is not useful for screening hybrid individuals between H. rufescens and H. fulgens. Furthermore, they produced the hybrid H. rufescens $ · H. fulgens # and identified both parental chromosomes in the hybrid offspring using genomic in situ hybridization (GISH), indicating that this technique permits accurate determination of the putative hybrid nature of early breeding material ).…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…However, it was absent from the black and green species and it was suggested that this DNA satellite sequence could be used to identify hybrids. However, Hernández‐Ibarra et al. (2008) discovered that SalI is also found in green abalone ( H. fulgens ) and is not useful for screening hybrid individuals between H. rufescens and H. fulgens .…”
Section: Genetic Certification Of Hybrid Status Among Abalone Speciesmentioning
confidence: 99%